A root specific induction of carotenoid biosynthesis contributes to ABA production upon salt stress in arabidopsis. - M Águila Ruiz-Sola; Vicent Arbona; Aurelio Gómez-Cadenas; Manuel Rodríguez-Concepción; Antía Rodríguez-Villalón (PLoS ONE, 2014)
Abscisic acid (ABA) is a hormone that plays a vital role in mediating abiotic stress responses in plants. Salt exposure induces the synthesis of ABA through the cleavage of carotenoid precursors (xanthophylls), which are found at very low levels in roots. Here we show that de novo ABA biosynthesis in salt-treated Arabidopsis thaliana roots involves an organ-specific induction of the carotenoid biosynthetic pathway. Upregulation of the genes encoding phytoene synthase (PSY) and other enzymes of the pathway producing ABA precursors was observed in roots but not in shoots after salt exposure. A pharmacological block of the carotenoid pathway substantially reduced ABA levels in stressed roots, confirming that an increase in carotenoid accumulation contributes to fuel hormone production after salt exposure. Treatment with exogenous ABA was also found to upregulate PSY expression only in roots, suggesting an organ-specific feedback regulation of the carotenoid pathway by ABA. Taken together, our results show that the presence of high concentrations of salt in the growth medium rapidly triggers a root-specific activation of the carotenoid pathway, probably to ensure a proper supply of ABA precursors required for a sustained production of the hormone.